Digital Cognition and Epistemic Beliefs: How Pre-Service Primary Teachers Construct Mathematical Knowledge - Maulida, Aya Shofia; Wahyudin; Turmudi (IKIP Siliwangi, 2026)
The increasing integration of digital technology in teacher education has reshaped how future teachers engage with knowledge and learning. This study explores how pre-service primary mathematics teachers conceptualize knowledge within digital learning environments and examines the relationship between their epistemic beliefs and digital engagement. A quantitative descriptive design was employed involving 34 undergraduate students enrolled in a primary teacher education program at an Indonesian university. Data were collected using a 20-item questionnaire adapted from Schommer’s Epistemological Beliefs framework and contextualized to reflect digital learning experiences. The instrument measured beliefs concerning the certainty, simplicity, and source of knowledge, as well as perceptions of learning ability and learning processes. Responses were analyzed using descriptive statistics. The findings indicate that participants predominantly hold constructivist-oriented epistemic beliefs, viewing knowledge as interconnected, evolving, and shaped through reflection and experience. Digital technology was generally perceived not merely as an instructional aid but as a medium that supports pedagogical thinking and professional growth. Statements reflecting growth-oriented learning and independent knowledge construction received strong agreement, whereas fixed and authority-dependent beliefs were largely rejected. These results suggest that epistemic sophistication may support more reflective and meaningful digital engagement. The study highlights the importance of integrating epistemological development with digital competence in teacher education to foster adaptive and reflective future educators.